Hepatectomy for benign and malign diseases in University Hospital - Carvalho, Marilia Daniela Ferreira; Araújo-Filho, Irami; Rêgo, Amália Cínthia Meneses; Azevedo, Ítalo Medeiros; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2011)
Purpose: The hepatectomy is a surgical modality for the treatment of benign and malignant liver diseases. This retrospective study aimed to analyze the main clinical and technical aspects concerning 33 hepatectomies performed from July 2006 to July 2010, at Onofre Lopes University Hospital, Federal University of Rio Grande do Norte, Brazil. Methods: The patients informations were stored in the program 2000 MV ®, developed by MV Software & Consulting. The data of interest for the work were organized in tables, and these were processed in the Microsoft Office Excel ® 2010 for the construction of statistical data and graphs. Demographic data included gender, origin, age and co-morbidities. Hepatectomy was categorized as anatomical resection and nonanatomical resection. A curative hepatectomy was defined as a case without macroscopic evidence of residual tumor. All patients that underwent hepatectomy were computed. The prevalence of complications was calculated. Statistics: all continuous results were presented as the median (range). All categorical results were presented as percentage. Results: We did not find difference in the prevalence of gender. The most prevalent comorbidity and postoperative complication was arterial hypertension (30%) and fistula (18%), respectively. Forty five percent of patients had no comorbidity. Mortality was 12%. Twenty one percent of patients had gallbladder cancer and 12% had metastasis of colon cancer. Hepatocellular carcinoma occurred in 6% of patients and iatrogenic lesions of the bile duct in 3% of cases. Anatomical resection predominated (n=25; 75.7%). Seven of them (21.2%) underwent major resection exceeding hemihepatectomy, and 4 underwent extended bi-segmentectomy. Eight patients (24.3%) underwent non-anatomical (atypical) resections. Conclusion: These data showed morbidity and mortality posthepatectomy compatible with literature and that radiological and functional assessment permited hepatectomy including anatomic resection and optimal pathologic margins. Measures to minimize postoperative morbidity were implemented.